Socioeconomic Determinants of Household Investment Portfolio in India. (September 2022) - Rampal, Priya; Biswas, Shreya
This study examines the determinants of asset holding by low- income households in India using the second wave of the Indian Human Development Survey. Our exploratory analysis indicates that even low-income households seem to hold portfolios that are in line with financial goals such as education and marriage. Employing parametric and non-parametric methods, the study finds that affordability is one of the critical predictors of asset holding by households. Further, we find that higher educational attainment, being more socially connected and having confidence in financial institutions are positive predictors of individual asset holding and the likelihood of holding a diversified portfolio. The study discusses policy implications emanating from the findings for designing financial products along with improving penetration.